PELAKSANAAN BAURAN PROMOSI PAKET WISATA PADA CV BILAVA TOUR - Rofif Murtadho; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The tourism sector is a sector that has the potential to be developed as a source of regional income. The development and utilization program of regional tourism resources and potential is expected to contribute to economic development since the Covid-19 hit, a lot of tourism has been lost due to adverse impacts. One of Tour&Travel that is still running well in the midst of the COVID-19 pandemic is CV Bilava Tour, which is one of the BPWs which is a BPW which has various tour packages sold for families, government groups and so on. do not yet have adequate promotions and tourism targets, especially to promote their tour packages. Promotion is a one-way flow of information or persuasion or is made to direct an organization or person to actions that create exchanges in marketing by planning and implementing a good promotional strategy that will also increase the income of Bilava Tour. Therefore, this study aims to find out how to implement the promotion mix Tour Packages on Bilava Tour. This study uses a qualitative descriptive method to analyze problems based on data collection techniques in the form of observation, in-depth interviews, and documentation. The Promotion Strategy includes reporting on conditions carried out in advertising, direct marketing, public relations and personal selling. Based on the results of the research that has been carried out, for the entirety of the results of observations and interviews, it can be concluded that the Implementation of the Tour Package Promotion Mix for the Bilava Tour during the Covid-19 Pandemic has not fully worked out as targeted, although there are still shortcomings. Keywords: Promotional Mix, Tour Packages